SINERGI KOMUNITAS DAN PERLINDUNGAN ANAK: UPAYA KOLEKTIF PENCEGAHAN STUNTING MELALUI PEMBERDAYAAN MASYARAKAT BERKELANJUTAN - Aminatur Rosyidah; Zulfi Zumala Dwi A; Elok Hidayah; Asna Zunairoh; Dwi Swastanti R (Yayasan Bakti Cendekia Nusantara, 2025)
Stunting is still a serious health problem in Barurejo Village, Banyuwangi, with the main causative factors being a lack of parental understanding of nutrition, non-optimal parenting, and non-educative use of gadgets. This community service activity aims to increase community awareness through interactive counseling, training in making nutritious complementary food, and community-based mentoring. The implementation methods include parenting education, the formation of a Village Stunting Working Group (Pokja), and the “Healthy Yard” initiative for family food security. The results showed a significant increase in parents' understanding (85%) of stunting, the formation of 15 trained cadres, and the optimization of gadgets as a medium for health education. This activity also encouraged the village government's commitment to allocate special funds for stunting prevention programs. Long-term impacts include a technology-based monitoring system through the “Sehat Barurejo” application and expansion of the intervention model to neighboring villages. This program proves that a community-based participatory approach is effective in reducing the risk of stunting in a sustainable manner.